Doctor who? Who gets admission offers in UK medical schools - Wiji Arulampalam; Robin A. Naylor; Jeremy P. Smith (Institute for the Study of Labor (IZA), 2005)
In the context of the UK Government's ambitious programme of medical school expansion, it is important to have an understanding of how the medical school admissions process works, and with what effects. The issue is also relevant for the Schwartz Review (2004) into higher education admissions. Using individual-level data for two entire cohorts of medical student applicants in UK universities and exploiting the panel structure of the applicant-medical school information, we estimate models to analyse the probability that an individual student receives an offer of a place. We find that prior qualifications, school type, gender, age, social class and ethnic background are major influences on whether a student receives an offer from a medical school. We also find that the probability of receiving an offer from a particular medical school is influenced by the identity of other medical schools applied to. Finally, we find evidence that certain groups of applicants are particularly disadvantaged the later they apply within the application process.
Keywords: J24; I2; C41; 330; medical students; admissions; offer (non-rejection) probabilities; endogenous selection; unobserved heterogeneity